Cotas raciais: uma análise empregando o Enade 2016 a 2018 à luz da economia da educação - Santos, Priscila Soares dos (2021)
Education is capable of providing private and collective returns in a society. Public higher education institutions, as promoters of teaching, extension and research activities, play an important role in this process. Bearing in mind that these institutions are maintained with public resources, the importance of analyzes that contemplate both the quality of education accessed by society, and its effects, is highlighted. In this study, we sought to analyze, at first, which factors are capable of influencing the quality of Brazilian public higher education, measured as academic performance. For this, a two-level hierarchical model was estimated: students and courses. It was observed that both factors related to the characteristics of the students and the heterogeneity of the courses are capable of affecting the quality of teaching. In a second step, the objective was to assess the impact of racial quotas for higher education on academic performance, time and delay in completing the course. Through public policy impact assessment models, it was possible to verify a negative impact, albeit small, on performance, but in most of the estimates used, no impacts were found on the time or delay in completing higher education. Finally, we sought to analyze and the quota policy for higher education based on racial ethnic criteria in Brazil has already gone through the institutionalization process. As politics is subject to criticism and social challenges, attention is drawn to the possibility of it being removed before its goals are achieved, for example, in times of political instability. Based on a fuzzy inference systems approach, a Contest Index for Criticisms of Racial Affirmative Actions was estimated based on three of the main arguments of those who are against politics: student performance, time take to graduate and the family income of those affected by the quotas. It was possible to build an index considered high, which indicates that, according to the arguments used against the policy, there is a high power of contestation. This, in a way, corroborates the results of the trial that assesses the impact of the policy on the quality of higher education. In all the analyzes carried out, the database used was that comprising the Enade microdata in the time frame from 2016 to 2018.